Diversity and distribution of avifauna in wetland ecosystems (Zoological Records and Reviews, 2022)
Wetland ecosystems support a disproportionately high proportion of global avian diversity relative to their limited spatialextent, serving as critical habitats for resident waterbirds, migratory shorebirds, and wintering wildfowl along the Centraland East Asian flyways. The inland wetlands of the Deccan Plateau and coastal wetlands of the Eastern Indian coastlinerepresent globally significant nodes in the Central Asian Flyway, yet comprehensive multi-year avifaunal surveys withquantitative distribution data remain sparse for this region. This study documents the diversity and distribution of avifaunaacross 28 wetland ecosystems spanning inland reservoirs, coastal lagoons, mangroves, and flooded agriculturalwetlands in Andhra Pradesh, Telangana, and Odisha, surveyed using standardised point counts and distance samplingtransects over three complete annual cycles (2019-2022). A total of 312 bird species from 58 families are documented,comprising 184 resident breeding species and 128 migratory or seasonal visitors. Waders (Charadriiformes: 64 species)and herons/egrets (Ardeidae: 22 species) are the most species-rich groups. Wetland area, hydroperiod stability, andsurrounding agricultural land use are the three strongest predictors of avian species richness. Chilika Lake contributesthe highest single-wetland species richness (218 species over the study period). Twenty-four species are IUCNThreatened or Near Threatened. Key populations of the globally threatened Greater Adjutant (Leptoptilos dubius),Black-necked Stork (Ephippiorhynchus asiaticus), and Indian Skimmer (Rynchops albicollis) are documented.Conservation and management recommendations are presented for priority wetland sites.